The Impact of COVID-19 Vaccination Side-Effects on Work Attendance among Saudi Healthcare Workers - Jawaher Alguraini; Mohamed T. S. Saleem; Nahed N. Mahrous; Abbas Shamsan; Fatima Zia Zaidi; Ohoud S. Alhumaidan; Yahya F. Jamous (MDPI AG, 2024)
Objective: This cross-sectional-survey-based study aimed to investigate the severity of side-effects from Coronavirus disease (COVID-19) mRNA (Pfizer, Moderna), viral vector DNA (Oxford-AstraZeneca, J&J/Janssen), inactivated virus (Sinopharm, Sinovac), and other vaccines among healthcare workers (HCWs) in Saudi Arabia, focusing on their impact on work attendance. Methods: A total of 894 HCWs residing in Saudi Arabia participated in this study from March 2023 to May 2023. Participants completed an online questionnaire assessing demographic information, vaccination status, comorbidities, vaccine side-effects, and missed work information after vaccination. Descriptive statistics and chi-square tests were used for data analysis. Results: The majority of participants were female (83.7%) and aged 25-34 years (42.8%). Most participants were predominantly vaccinated with mRNA vaccines. Common side-effects included pain at the injection site, fatigue, fever, and chills. However, no significant association was found between vaccine type, side-effects, and work absenteeism. While demographic factors such as age and healthcare profession did not influence work absenteeism, variations were observed among different racial groups. Conclusion: COVID-19 vaccination among HCWs in Saudi Arabia is associated with common side-effects, but their impact on work attendance is not significant. Understanding these implications can inform strategies to support the healthcare workforce and mitigate the impact on patient care and staffing during the ongoing COVID-19 pandemic.